Psychosis and alterations in sensory perception as atypical manifestations of microscopic polyangiitis (2019)
Microscopic polyangiitis is a systemic anti-neutrophil cytoplasmic antibody-associated vasculitis, and is associated with the necrotising small calibre vessels. Its clinical manifestations are varied, and the most severe forms manifest with rapidly progressive glomerulonephritis and pulmonary capillaritis. In the nervous system, it mainly involves the peripheral system. Involvement of the central nervous system is not common, and clinical findings of psychosis and behaviour alterations are infrequent. © 2019 Asociación Colombiana de Reumatología